2022
DOI: 10.1371/journal.pone.0273695
|View full text |Cite
|
Sign up to set email alerts
|

AGO104 is a RdDM effector of paramutation at the maize b1 locus

Abstract: Although paramutation has been well-studied at a few hallmark loci involved in anthocyanin biosynthesis in maize, the cellular and molecular mechanisms underlying the phenomenon remain largely unknown. Previously described actors of paramutation encode components of the RNA-directed DNA-methylation (RdDM) pathway that participate in the biogenesis of 24-nucleotide small interfering RNAs (24-nt siRNAs) and long non-coding RNAs. In this study, we uncover an ARGONAUTE (AGO) protein as an effector of the RdDM path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…AGO4 and its paralogs (AGO6 and AGO9) have been extensively studied in Arabidopsis using mutants (Havecker et al 2010 ; Duan et al 2015 ; Wang et al 2023 ). Contrarily, in monocotyledons, only rice and maize orthologs have been experimentally studied (Nonomura et al 2007 ; Kapoor et al 2008 ; Qian et al 2011 ; Yang et al 2013 ; Li et al 2019 ; Zhai et al 2019 ; Aubert et al 2022 ). Rice was found to have four different members of the AGO4 clade, namely AGO4A, AGO4B, AGO15, and AGO16.…”
Section: Introductionmentioning
confidence: 99%
“…AGO4 and its paralogs (AGO6 and AGO9) have been extensively studied in Arabidopsis using mutants (Havecker et al 2010 ; Duan et al 2015 ; Wang et al 2023 ). Contrarily, in monocotyledons, only rice and maize orthologs have been experimentally studied (Nonomura et al 2007 ; Kapoor et al 2008 ; Qian et al 2011 ; Yang et al 2013 ; Li et al 2019 ; Zhai et al 2019 ; Aubert et al 2022 ). Rice was found to have four different members of the AGO4 clade, namely AGO4A, AGO4B, AGO15, and AGO16.…”
Section: Introductionmentioning
confidence: 99%
“…Together, these genetic studies show that, similar to other cases of maize paramutation ( Dorweiler et al 2000 ; Alleman et al 2006 ; Erhard et al 2009 ; Stonaker et al 2009 ), establishment of p1 paramutation depends on RNA-mediated silencing mechanisms, while maintenance of P1-rr′ silencing has distinct genetic requirements that would benefit from additional studies. These additional studies may include factors that have been shown to regulate pl1 and b1 paramutations, including but not limited to PICKLE-like chromodomain DNA-binding 3 (CHD3) protein that is required to maintain pl1 paramutation but is dispensable for maintenance of b1 paramutation ( Deans et al 2020 ) and AGO104 that disrupts b1 paramutation ( Aubert et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additional proteins implicated in the repression of B´ include a putative maize ortholog of Arabidopsis ARGONAUTE9 (AGO9) (a member of the AGO4 clade), ZmAGO104, [ 43 ] and a novel protein isoform encoded by the unstable factor for orange1 ( ufo1 ) locus [ 44 , 45 ]. A dominant Ufo1-1 allele enhances the expression of both repressed B´ and p1 alleles through an unknown mechanism [ 44 ].…”
Section: Introductionmentioning
confidence: 99%